B-mode real time ultrasonography for early pregnancy diagnosis in Osmanabadi goats - DEOKATE, K R; DHOBLE, R L; GAIKWAD, S M; SAWALE, A G; JUVEKAR, J C (The Indian Journal of Animal Sciences, 2011)
The present study was carried out to study the accuracy of ultrasonographic pregnancy diagnosis in Osmanabadi goats. For this study 40 does synchronized and bred naturally were selected. The ultrasonographic examination ’was carried from day 8- post breeding. Out of these 40 ewes, 25 ewes were pregnant which were confirmed later by kidding. The accuracy of positive pregnancy diagnosis on day 10-post breeding was 16%, on day 17 was 76% and on day 24 was 100%. Â